Tuberculosis of the Cervix – Mimicking Cervical Cancer - Chaurasia, A; Tyagi, K; Dhingra, V (Nepal Journal of Obstetrics and Gynaecology, 2015)
We present a case of tuberculosis of the cervix due to the rarity of this condition and its clinical resemblance to a dreadful disease, “carcinoma of cervix.”